Walking the tightrope. Combining family life, career and job mobility - Detlev Lück (Journal of Family Research, 2010)
The article examines the ways in which job mobility affects the relationship between dual careers and parenthood and the ability of couples to realise both. Based on survey data from the project Job Mobilities and Family Lives in Europe for six countries (Germany, France, Spain, Poland, Switzerland, Belgium), bivariate analyses compare ratios of couples with children and/or one or two careers between couples confronted with job mobility in the husband’s or wife’s job and those who have no such mobility. Multivariate analyses test the influence of job mobility and other relevant circumstances on female employment as well as on having children. Indicators measuring respondents’ subjective evaluation of the influences are reviewed to confirm the results. The results suggest that couples tend to be childless rather than give up one partner’s job if the two goals are incompatible. Job mobility, as with other unfavourable circumstances, reduces the ability of couples to combine both, and this ability is much more reduced if the woman is job mobile than if the man is. In addition, national context matters for level of compatibility and for strength of effects.